Virulence and Host Range of Fungi Associated With the Invasive Plant Ageratina adenophora - Lin Chen; Lin Chen; Ai-Ling Yang; Yu-Xuan Li; Han-Bo Zhang (Frontiers in Microbiology, 2022)
To determine whether disease-mediated invasion of exotic plants can occur and whether this increases the risk of disease transmission in local ecosystems, it is necessary to characterize the species composition and host range of pathogens accumulated in invasive plants. In this study, we found that Didymellaceae, a family containing economically important plant fungal pathogens, is commonly associated with the invasive plant Ageratina adenophora. Accordingly, we characterized its phylogenetic position through multi-locus phylogenetic analysis, as well as its environmental distribution, virulence, and host range. The results indicated that 213 fungal collections were from 11 genera in Didymellaceae, ten of which are known, and one is potentially new. Didymella, Epicoccum, Remotididymella, and Mesophoma were the dominant genera, accounting for 93% of total isolates. The virulence and host ranges of these fungi were related to their phylogenetic relationship. Boeremia exigua, Epicoccum latusicollum, and E. sorghinum were found to be strongly virulent toward all tested native plants as well as toward A. adenophora; M. speciosa and M. ageratinae were weakly virulent toward native plants but strongly virulent toward A. adenophora, thus displaying a narrow host range. Co-evolution analysis showed no strong phylogenetical signal between Didymellaceae and host plants. Isolates S188 and Y122 (belonging to M. speciosa and M. ageratinae, respectively) showed strong virulence toward A. adenophora relative to native plants, highlighting their potential as biocontrol agents for A. adenophora invasion. This study provides new insights into the understanding of the long-term ecological consequences of disease transmission driven by plant invasion.